Extracurricular Management of Traditional Dance in Accommoding The Talents Of Students' Interests at SDN Dinoyo 3 - Kristanto, Prayoga Dwi; Zulkarnain, Wildan; Nurabadi, Ahmad; Sunandar, Asep (Proceedings Series of Educational Studies, 2024)
The purpose of this research is to investigate the planning, organization, implementation, supervision, and evaluation, as well as the supporting factors, obstacles, and solutions of the traditional extracurricular dance management at SDN Dinoyo 3. This study employs a qualitative case study approach. The data collection methods used in this research include interviews, participatory observation, and documentation techniques. The main informants for this study are the extracurricular coordinator, school head, dance instructors, assistant dance instructors, Asmoro Bangun Dance Studio, teachers, guardians, and students. The research findings include (1) planning involves considering the background, determining the objectives, formulating the benefits, meetings with teachers and guardians, allocating facilities and equipment, drafting programs and materials, selecting instructors, and planning external collaborations; (2) organization involves an informal organizational structure and task and responsibility distribution; (3) implementation includes conducting activities, maintaining order, achieving achievements, preparing for competitions, appreciating achievements, developing dance habits, and creating a supportive environment for male students; (4) supervision and evaluation are carried out; (5) supporting factors are divided into two categories: general factors and factors related to male students participating in traditional dance extracurricular activities; and (6) obstacles include the assistant's lack of experience teaching elementary school students, students' interest in participating but guardians' disapproval, unequal practice times, lack of transportation during practice, ridicule of male students participating in traditional dance extracurricular activities, and negative perceptions of male students. The solutions proposed are the extracurricular assistant should be more firm, approach guardians with empathy, one party should compromise, offer transportation from Mr. Budi, provide encouragement and motivation to students, and gather guardians to provide understanding. Keywords: extracurricular management; traditional dance; talent interest